Development and Validation of Critical Thinking Skills Instruments on Mechanical Waves for Senior High School Student - Azizah, Fithrotul; Handayanto, Supriyono Koes; Wisodo, Hari; Fernando, Trio Junira; Kuswanto, Kuswanto; Prani, Anisak Intan Eka (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
The importance of developing critical thinking skills (CTS) is claimed as a major education purpose. Recently, enhanced learning has been conducted to promote students' CTS through study on certain topics (specific domains). Based on the numerous studies on CTS, there is a need for an assessment instrument to test students' CTS. This research aims to develop an instrument of CTC on mechanical wave topics for senior high school students. The instrument consists of seven essay items and one forced-choice item, tested to 45 students of class XI high school in Malang. The validity test obtained an excellent Cronbach alpha coefficient of ? = 0.717. There was also an inter-rater test for the scoring guideline reliability using the intraclass correlation coefficient (ICC) with high reliability results (? = 0.909). The results of this study indicate that the instrument is qualified to be used to measure students' CTS on mechanical wave topics.